The effect of nonsurgical periodontal treatment on serum and saliva chitotriosidase activities in patients with periodontitis and coronary artery disease - Bal MV; Olgun A; Abaslı D; Özdemir A. Kürşaklıoğlu H; Göktepe AS; Kurt Í (Dove Medical Press, 2014)
Mehmet Vehbi Bal,1 Abdullah Olgun,2 Dilek Abasli,3 Atilla Özdemir,1 Hürkan Kürsaklioglu,4,† Ahmet Salim Göktepe,5 Ísmail Kurt3 1Department of Periodontology, 2Biochemistry Laboratory, TSK Rehabilitation Center, 3Department of Biochemistry and Clinical Biochemistry, 4Department of Cardiology, 5Department of Orthopedics, TSK Rehabilitation Center, Gülhane Military Medical Academy, Ankara, Turkey †Hürkan Kürsaklioglu passed away on July 17, 2012 Background: Plasma chitotriosidase activity, which is a marker of macrophage activation, has been reported to increase in inflammatory conditions and atherosclerosis. Chronic periodontitis has likely an important role in the development of coronary artery disease. In this study, we aimed to analyze the effect of chronic periodontitis on salivary and plasma chitotriosidase activities in patients with or without coronary atherosclerosis.Methods: Fifty subjects were divided into four groups as controls (n=13), periodontitis (n=11), coronary artery disease (n=13), and periodontitis + coronary artery disease (n=13). Plasma and saliva chitotriosidase activities were measured by a fluorimetric method in all groups before the nonsurgical treatment of periodontitis and 5 weeks posttreatment in periodontitis groups.Results: Salivary chitotriosidase activity was decreased after nonsurgical periodontal treatment in patients having periodontitis with or without coronary atherosclerosis. However, plasma activities remained unchanged.Conclusion: Although this study has some limitations like small sample size and short study duration, it can suggest that salivary chitotriosidase can have the potential to be used as a very useful and practical marker to evaluate the success of the periodontal treatment and/or host response.Key finding: Salivary chitotriosidase can be used as a marker for the evaluation of the success of the periodontal treatment and/or host response. Keywords: chitotriosidase, chronic periodontitis, coronary artery disease, nonsurgical periodontal treatment